The Utility of Ground Bryophytes in the Assessment of Soil Condition in Heavy Metal-Polluted Grasslands - Rola, Kaja; Plášek, Vítězslav (Plants (Basel, Switzerland), 2022)
Bryophytes are commonly used in biomonitoring heavy metal pollution, whereas the bioindicative value of bryophyte communities is a less known issue. The aim of the present study is to recognize the utility of the bryophyte community's structure in the assessment of soil condition in heavy metal-polluted, dry grasslands. The study plots are examined with respect to bryophytes; vascular plants; concentrations of Zn, Pb, Cd, and As in the soil; total nitrogen and organic carbon content in the soil; and soil pH. The results show that both bryophyte species richness and composition greatly depend on soil chemical characteristics, including heavy-metal pollution levels and soil pH. Three groups of species are distinguished: (1) species sensitive to pollution growing on acidic soils, (2) nonspecific species inhabiting a wide spectrum of heavy metal-polluted sites, and (3) species preferring polluted and alkaline soils. Our study reveals a gradual replacement of the bryophyte species alongside increasing soil pollution and alkalinity. This proves that bryophytes are highly responsive to soil factors and the changes in bryophyte composition may indicate the soil condition of a certain site. Furthermore, high concentrations of heavy metals in the soil and an alkaline pH positively affect bryophyte species richness. Consequently, such sites could be considered as biodiversity hotspots for terrestrial bryophytes in post-industrial landscapes.
Keywords: soil pollution; bioindication; species richness; soil pH; bryophytes; heavy metals